2008
DOI: 10.4102/sajip.v34i2.427
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual framework of integrity

Abstract: This article reports on the fndings of a qualitative study in which the construction of integrity of some business leaders was explored. Data were gathered through ten in-depth interviews with six South African business leaders commended to be champions of integrity. A grounded-theory approach to the data analysis elicited fve themes. These themes and their interrelatedness are discussed in this article and a conceptual framework of integrity is proposed. Integrity is conceptualised as a multifaceted and dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 57 publications
(50 reference statements)
1
31
0
3
Order By: Relevance
“…The personal inner drive (desires, needs, ambitions and goals) can also act as a possible threat to integrity because personal desires, needs and ambitions may lure an individual to act only in the interest of oneself, dishonestly. 29 Other factors expediting plagiarising and cheating include: students' perception that it is easy to get away with it as universities do 'not chase it up'; different methods of assessment offer different chances for plagiarising and cheating; and students consider cheating is justifiable when teaching and assessments are of poor quality. Importantly, the quality of the student experience is a priority; and lastly, teaching of large classes can result in students feeling neglected and alienated in the system.…”
Section: Factors Influencing Student Plagiarismmentioning
confidence: 99%
See 1 more Smart Citation
“…The personal inner drive (desires, needs, ambitions and goals) can also act as a possible threat to integrity because personal desires, needs and ambitions may lure an individual to act only in the interest of oneself, dishonestly. 29 Other factors expediting plagiarising and cheating include: students' perception that it is easy to get away with it as universities do 'not chase it up'; different methods of assessment offer different chances for plagiarising and cheating; and students consider cheating is justifiable when teaching and assessments are of poor quality. Importantly, the quality of the student experience is a priority; and lastly, teaching of large classes can result in students feeling neglected and alienated in the system.…”
Section: Factors Influencing Student Plagiarismmentioning
confidence: 99%
“…These were consistent with some of the factors influencing student plagiarism identified in the literature. 21,29 Academics revealed that they only used Turnitin as a plagiarism detection strategy as it is university policy. They agreed that the university policy on plagiarism is 'too lenient' (Tony), and that there are 'no punitive measures in place to deal with this gross misconduct by students' and reports of incidences are not adequately followed up (Pearl).…”
Section: Class Size Matters: Academics' Experiences Of Plagiarism In mentioning
confidence: 99%
“…Academic integrity in the domain of positive psychology is included in positive personality constructions that address issues of plagiarism, ethics and writing (Barnard, Schurink & Beer, 2008;Pfannenstiel, 2010). Academic integrity according to McCabe (in CAI, 1999, p.4) is a commitment to five basic values, namely honesty, trust, fairness, respect, and responsibility.…”
Section: Introductionmentioning
confidence: 99%
“…Bravery is exhibited in a form of being brave to openly uphold the truth with confidence [9] (adapted from Modul Muatan Lokal Diklat Teknis dan Fungsional, 2017). In the positive-psychology domain, integrity has also been linked to positive personality constructs, such as courage, care, authenticity and honesty [10]- [12].…”
Section: Introductionmentioning
confidence: 99%